Conocimientos y mitos sobre menopausia en mujeres de edad fértil que acuden a consulta externa del Hospital General Isidro Ayora Noviembre 2018-Abril 2019 - Rodas Cartuche, Gabriela Fernanda (2019)
Menopause is a stage of women, characterized by bringing a series of physiological, psychic, social and cultural changes, puts an end to the reproductive capacity of women. This descriptive study called "KNOWLEDGE AND MYTHS ABOUT MENOPAUSE IN FEMALE AGE WOMEN THAT COME TO EXTERNAL CONSULTATION OF THE ISIDRO AYORA HOSPITAL", whose objective was to determine the level of knowledge and myths about menopause in women of childbearing age who come to external consultation of the Isidro Ayora Hospital during November 2018-April 2019. The universe consisted of 207 women who attended the outpatient clinic; the instrument used was a survey and the presentation of the data was carried out in simple and crossed frequency tables. The analysis was based on the bibliography of the theoretical framework; obtaining as main results; the largest number of women participating are between the ages of 30 and 39. In terms of occupation, the highest percentage were housewives. In relation to knowledge, it was determined that 57.97% identify the age of onset of menopause, 60.39% know the definition, 76.33% know what the signs and symptoms are, however, near the 60% don’t know the phases. Concerning to the myths, women in their different levels of schooling showed that, 27.07% of women have multiple ailments, 21.26% have a higher risk of breast cancer; and 15.94% think that women during menopause are more vulnerable to suffer "madness" Key words: knowledge, myths and menopause.